Language and Print Concepts Achievement among Children with Low and High Reading Motivation. Issue 7 (6th October 2021) - Vaknin-Nusbaum, Vered; Nevo, Einat; Gilat-Yihyie, Sharon
Abstract: This study investigates the relationships between reading motivation, language ability, and print-concept skills among Hebrew-speaking kindergarteners, before they are formally exposed to reading instruction. The purpose of the study was to explore reading motivation-literacy relationships and to determine whether there are differences in language and print concepts achievement between children with low versus high reading motivation. One hundred and ten kindergarteners participated in the study, and were assessed at the beginning of the school year. It was found that reading motivation had a unique contribution to children's achievements in language and print concepts knowledge, and predicted success in those literacy domains. Highly motivated children had higher scores in language and print concepts as compared to their lower-motivated peers. The results suggest that reading motivation is an essential predictor of language and literacy skills at an early age, even before children are formally exposed to reading instruction. Implications for educators are further discussed.